N-ary trees classifier - Duque, Duarte (2006)
This paper addresses the problem of automatic detection and prediction of abnormal human behaviours in public spaces. For this propose a novel classifier, called N-ary trees, is presented. The classifier processes time series of attributes like the object position, velocity, perimeter and area, to infer the type of action performed. This innovative classifier can detect three types of events: normal; unusual; or abnormal events. In order to evaluate the performance of the N-ary trees classifier, we carry out a preliminary study with 180 synthetic tracks and one restricted area. The results revealed a great level of accuracy and that the proposed method can be used in surveillance systems.